A randomized, double-blind, placebo-controlled, parallel-group, enriched-design study of nabiximols (Sativex®), as add-on therapy, in subjects with refractory spasticity caused by multiple sclerosis - Novotna, A.; Mares, J.; Ratcliffe, S.; Novakova, I.; Vachova, M.; Zapletalova, O.; Gasperini, C.; Pozzilli, C.; Cefaro, L.; Comi, G.; Rossi, P.; Ambler, Z.; et al. (European journal of neurology, 2011)
Background:  Spasticity is a disabling complication of multiple sclerosis, affecting many patients with the condition. We report the first Phase 3 placebo‐controlled study of an oral antispasticity agent to use an enriched study design. Methods:  A 19‐week follow‐up, multicentre, double‐blind, randomized, placebo‐controlled, parallel‐group study in subjects with multiple sclerosis spasticity not fully relieved with current antispasticity therapy. Subjects were treated with nabiximols, as add‐on therapy, in a single‐blind manner for 4 weeks, after which those achieving an improvement in spasticity of ≥20% progressed to a 12‐week randomized, placebo‐controlled phase. Results:  Of the 572 subjects enrolled, 272 achieved a ≥20% improvement after 4 weeks of single‐blind treatment, and 241 were randomized. The primary end‐point was the difference between treatments in the mean spasticity Numeric Rating Scale (NRS) in the randomized, controlled phase of the study. Intention‐to‐treat (ITT) analysis showed a highly significant difference in favour of nabiximols (P = 0.0002). Secondary end‐points of responder analysis, Spasm Frequency Score, Sleep Disturbance NRS Patient, Carer and Clinician Global Impression of Change were all significant in favour of nabiximols. Conclusions:  The enriched study design provides a method of determining the efficacy and safety of nabiximols in a way that more closely reflects proposed clinical practice, by limiting exposure to those patients who are likely to benefit from it. Hence, the difference between active and placebo should be a reflection of efficacy and safety in the population intended for treatment. Click here to view the accompanying paper in this issue.